Estimulación intrauterina durante el tercer trimestre de Gestación en pacientes que acuden al Centro de Salud nº06d01 chambo - Riobamba, marzo - julio 2016 - Falconi Merizalde, Priscila Monserrath,Roberto Lema (2017)
Lumbar pain during pregnancy is one of the problems that pregnant women present, having a notable impact for the optimal management of the activities in their daily life, and during the gestation period. The research of Intrauterine Stimulation during the third trimester of gestation has been carried out on groups of pregnant women with distinct characteristics that attend Health Center Nº06D01 Chambo – Riobamba. This research is executed with the objective of applying intrauterine stimulation to third trimester patients to reduce lumbar pain, and thus improve the physical and mental health of women in the gestation process. This research corresponds to a field study. The inductive and deductive methods where use in 32 patients who were evaluated repeatedly to distinguish advances, and also to achieve reasonable results. During this process, and improvement was achieved in the values presented by the EVA scale, which evaluated the pain in the lumbar spine, concluding that the application of Intrauterine Stimulation during pregnancy leads to satisfactory results. Hence, the exercise even after delivery would help the mother’s full recovery.